Influence of different GaN cap layer thicknesses on electron mobility in AlN/GaN heterostructure field-effect transistors. (December 2016) - Cui, Peng; Liu, Huan; Lin, Zhaojun; Cheng, Aijie; Liu, Yan; Fu, Chen; Lv, Yuanjie; Feng, Zhihong; Luan, Chongbiao
Abstract: The AlN/GaN heterostructure field-effect transistors with different GaN cap layer thicknesses were fabricated. With the calculated electron mobility and polarization charge distribution, the influence of different GaN cap layer thicknesses on electron mobility was determined by experiment and theoretical calculation. It is found that the increase of the GaN cap layer thickness can weaken the polarization Coulomb field scattering, and improve the electron mobility. This would be a possible approach to improve the performance of AlN/GaN HFETs by choosing a proper GaN cap layer thickness. Highlights: The GaN cap layer can influence the electron mobility in AlN/GaN HFETs. This influence was determined by experiment and theoretical calculation. The thick cap layer can weaken PCF scattering and improve the electron mobility.